2004
DOI: 10.1590/s0100-40422004000400008
|View full text |Cite
|
Sign up to set email alerts
|

Degradação e estabilização do diclofenaco em nanocápsulas poliméricas

Abstract: Recebido em 2/6/03; aceito em 18/2/04; publicado na web em 17/06/04 DEGRADATION AND STABILIZATION OF DICLOFENAC IN POLYMERIC NANOCAPSULES. The parameters which affect the degradation and stabilization of diclofenac in suspensions of nanocapsules and of the corresponding spray-dried powders were investigated. Formulations were subjected to 14 months of storage at room temperature. In addition, a study of the degradation of diclofenac was carried out by exposing the formulations or mixtures (drug and adjuvants) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
(47 reference statements)
0
10
0
5
Order By: Relevance
“…The association rate varied from an initial 75.8% to 66.1% by day 120. According to Müller and co-workers, 51 such a decline in drug association efficiency in NC may be due to precipitation of nanocrystals of the drug during the formation of NC stabilized by surfactant agents. It was reported that these nanocrystals present the same size distribution as the NC, and therefore do not pass through the membrane used in the ultrafiltration/centrifugation procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The association rate varied from an initial 75.8% to 66.1% by day 120. According to Müller and co-workers, 51 such a decline in drug association efficiency in NC may be due to precipitation of nanocrystals of the drug during the formation of NC stabilized by surfactant agents. It was reported that these nanocrystals present the same size distribution as the NC, and therefore do not pass through the membrane used in the ultrafiltration/centrifugation procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results for polymer nanoparticle sizes have been reported in the literature. 50,51,53 Another parameter investigated was polydispersity, an index that can be indicative of stability, since it Physicochemical Stability of Poly(lactide-co-glycolide) Nanocapsules J. Braz. Chem.…”
Section: 552mentioning
confidence: 99%
“…O valor de SPAN foi empregado como medida da dispersão granulométrica, o qual relaciona os valores encontrados de diâmetros das partículas correspondentes a 10, 50 e 90% da distribuição acumulada para uma amostra. As medidas de d (4,3) foram calculadas a partir das determinações dos volumes médios das partículas. .…”
Section: Determinação Da áRea Superficial E Da Distribuição De Tamanhunclassified
“…1 Devido principalmente à sua fase aquosa, estas suspensões coloidais são bastante suscetíveis a alterações físico-químicas e contaminação microbiológica durante o armazenamento. 2,3 Nesse sentido, a secagem por aspersão (spray-drying) foi proposta por nosso grupo de pesquisa para a conversão desses sistemas dispersos aquosos em sistemas sólidos microparticulados, empregando o dióxido de silício coloidal (Aerosil  200) como adjuvante de secagem. Considerando que os fármacos antiinflamatórios não-esteróides têm sido foco de nossas pesquisas e que sua nanoencapsulação permite a redução significativa dos efeitos tóxicos de fármacos desta classe sobre a mucosa gastrintestinal, [4][5][6] demonstramos a aplicação desta téc-nica de secagem para a obtenção de produtos secos microparticulados a partir de diferentes tipos de nanopartículas poliméricas contendo indometacina ou diclofenaco.…”
Section: Introductionunclassified
“…Our study showed that besides the nature of the formulation, suspension or powder, the decrease in the drug content is dependent on the type and concentration of the surfactant system. An accelerate stability study carried out under UVC light exposition followed by mass spectrometry analysis demonstrated that 2-(2',6'-dichlorophenyl)aminobenzyl alcohol and N-(2',6'-dichlorophenyl)anthranilylaldehyde were the diclofenac degradation products [20].…”
Section: Drying Polymeric Nanoparticle Suspensionsmentioning
confidence: 99%